Meteorological data at the Thule High Arctic Atmospheric Observatory (THAAO_Met) - Muscari, Giovanni; Di Sarra, Alcide; Di Iorio, Tatiana; Pace, Giandomenico; Meloni, Daniela; Sensale, Gianpaolo; Calì Quaglia, Filippo; Iaccarino, Antonio (Agenzia Nazionale per le nuove tecnologie, l’energia e lo sviluppo economico sostenibile (ENEA), 2018)
Measurements of Pressure (P, in kPa), Temperature (T, in °C), and Relative Humidity (RH, in %) carried out by means of a Campbell meteorological station installed at the Thule High Arctic Atmospheric Observatory, near Thule Air Base (76.5°N, 68.8°W; 220m amsl), Greenland, in July 2016. The meteorological station is installed at 4 m above ground. Data are recorded at 10 minutes intervals and stored as ASCII textfiles.
THAAO_Met
Keywords: polar meteorology; Arctic amplification; Climate change